Online Learning: The Role Of Academic Self-Efficacy In Creating Academic Flow - Pantu, Eka Apristian (Psychological Research and Intervention, 2021)
The spread of Covid-19 encourages educational institution to maximize online learning. Online learning can work well if students are able to focus on learning. The ability to focus on learning is known as academic flow. This study aims to explain effect of academic self-efficacy on flow academic in online learning. This research involve 296 participants who were selected by incidental sampling. The instruments used in this research are self-efficacy scale and flow short scale which were analyzed by using linear regression techniques. The results shows that academic self-efficacy have a significant effect on academic flow (Î²=0,609; p=<0,001). This means that any increase in academic self-efficacy will have an impact on an increase in academic flow.